Congenital Portal Vein Aneurysm Associated with Peliosis Hepatis and Intestinal Lymphangiectasia. (10th February 2010) - Mungan, Zeynel; Pinarbasi, Binnur; Bakir, Baris; Gulluoglu, Mine; Baran, Bulent; Akyuz, Filiz; Demir, Kadir; Kaymakoglu, Sabahattin
Abstract : Portal vein aneurisym (PVA), peliosis hepatis (PH) and intestinal lymphangiectasia (IL) all are very uncommon entities. Herein, we presented a unique patient with these three rare entities who was admitted to our hospital because of portal hypertensive ascites rich in protein and lymphocyte. PVA was extrahepatic and associated with coronary vein aneurysm. Peliosis hepatis was of microscopic form. Lymphangiectasia was present in peritoneum and small intestine. Diagnoses of these rare entities were made by imaging techniques and histopathological findings. Patient also had hydronephrosis caused by ureteropelvic junction narrowing. Best of our knowledge, there is no such a case reported previously with the association of PVA, PH and IL. Therefore, we propose PVAPHIL syndrome to define this novel association.